Pulmonary embolism attenuation is a potential imaging biomarker for pulmonary artery hemodynamic improvement after catheter-directed thrombolysis. (April 2018) - Takahashi, Edwin A; Reisenauer, Christopher J; Stockland, Andrew H; Bjarnason, Haraldur; Neisen, Melissa J; Neidert, Newton B; Harmsen, William S; Day, Courtney N; Misra, Sanjay
This study examined the potential correlation between pulmonary embolism (PE) attenuation on computed tomography pulmonary angiography (CTPA) and pulmonary artery hemodynamic response to catheter-directed thrombolysis (CDT) in 10 patients with submassive PE. Treatment parameters, PE attenuation, clot burden, computed tomography signs of right ventricle dysfunction and right ventricular systolic pressure at echocardiography were retrospectively analyzed to determine correlation with pulmonary artery pressure improvement using Spearman correlation. A single reader, blinded to the treatment results, measured PE attenuation of all patients. There was a significant positive correlation between PE attenuation and absolute pulmonary artery pressure improvement with a Spearman correlation of 0.741, p =0.014. When attenuation was greater than or equal to the median (44.5 HU, n =5), CDT was associated with significantly better pulmonary artery pressure improvement ( p =0.037). Clot attenuation at CTPA may be a potential imaging biomarker for predicting pulmonary artery pressure improvement after CDT.